1995
DOI: 10.1111/j.1553-2712.1995.tb03597.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Quality Improvement Methods on Reducing Triage to Thrombolytic Interval for Acute Myocardial Infarction

Abstract: Objectives:To assess the timeliness of thrombolytic therapy in the ED for selected patients with acute myocardial infarction (AMI) following continuous quality improvement (CQI) interventions. Methods:A retrospective, historical comparison study was performed of triage-to-thrombolytic time intervals for AM1 patients using chart review for data collection. Patients treated after implementation of the CQI process vs a historical control group were compared. The patients with AM1 who had received thrombolytics du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…10 Lastly, there is a high likelihood that our stroke QI program influenced the use and safety of intravenous tPA in our hospital system, as has been demonstrated with thrombolytic therapy for myocardial infarction. 11 Our results suggest that intravenous tPA can be given safely to appropriate stroke patients at the community hospital level and that community physician performance improves over time.…”
Section: Discussionmentioning
confidence: 63%
“…10 Lastly, there is a high likelihood that our stroke QI program influenced the use and safety of intravenous tPA in our hospital system, as has been demonstrated with thrombolytic therapy for myocardial infarction. 11 Our results suggest that intravenous tPA can be given safely to appropriate stroke patients at the community hospital level and that community physician performance improves over time.…”
Section: Discussionmentioning
confidence: 63%
“…[42][43][44][45] Once patients arrive for care, the in-hospital phase of delay to treatment is small compared with the other phases. 46 The longest phase of delay continues to be the time from symptom recognition to the decision to seek care, and it is in this phase that the most improvement could be achieved. …”
mentioning
confidence: 99%
“…For example, Clawson and colleagues recently reported that, by providing emergency medical dispatchers with regular and objective performance feedback for a two-month period, their mean overall compliance score with dispatch protocols increased from 76% to 96%. 4 Other relevant ED CQI projects have been published, describing improvements in doorto-drug thrombolytic intervals, 5,6 EMS documentation, 7 patient length of stay and walkouts, 8,9 stat laboratory services, 10 radiograph callbacks, 11 and ED triage. 12 Our approach was to incorporate basic and time-proven CQI methodology into our initiative.…”
Section: Discussionmentioning
confidence: 99%